Henoch-Schönlein purpura in childhood: treatment of rapidly progressive glomerulonephritis with immunosuppressive anticoagulant therapy - Mocan, Hilal; Murphy, Anna V.; Beattie, T. James; Gibson, A. Angus (The Turkish Journal of Pediatrics, 1988)
Ten patients with rapidly progressive glomerulonephritis (RPGN) were treated with prednisolone, azathioprine or cyclophosphamide, dipyridamole, heparin and/or warfarin for periods of 1.7 weeks to 144 weeks with a mean period of 44 weeks. Three patients responded well, their mean glomerular filtration rate before treatment being 31.7 ml/min/1.73 m² to a mean of 111 ml/min/1.73 m² after treatment, the follow-up period being 45.3 months. Three patients had a partial response, showing a temporary rise in GFR and four patients had no response. Our observations suggested that this combined therapy has a place in patients with RPGN, especially in those patients where at the start of the treatment GFR is more than 20 ml·min/1.73 m², oliguria is absent and where crescents on renal biopsy are predominantly cellular. The incidence of side effects was high and it is necessary that the therapy be used with caution.